The Urgency of Halal Labelling for MSMEs in the Culinary Industry: Evidence from Demak Indonesia - Anita Rahmawaty; Eni Kusrini (Genius Journals, 2024)
This study aims to scrutinize the critical need for halal labeling for the community, particularly Muslim MSMEs stakeholders in the culinary industry. As a result, it can be used as a reference for obtaining halal product certification from the certified authority. This study also contributes to culinary MSMEs owners in improving product quality for customers' satisfaction. For MSME customers, halal labeling provides a level of trust and comfort in consuming culinary products. This study employs a descriptive qualitative method and elicited the data by interviewing MSME owners and consumers in Demak Regency, Indonesia. The results reveal that products with halal certification reflect higher levels of hygiene, making them superior products. Moreover, these certified products are able to gain access to the targeted market as requested by culinary MSME owners. Culinary MSME owners in the culinary industry possess an understanding of the procedures required for obtaining halal certification. In addition to culinary MSME owners, consumers also need halal labels as part of an integration process that combines information regarding potential habits, such as purchasing decisions. Therefore, the use of halal labeling can benefit all involved culinary MSME stakeholders
Keywords: Halal labeling; Halal culinary products; MSME stakeholders